The Ways of Lecturers’ Professional Self-Improvement at Higher Educational Establishments - Halyna Lysak (Pedagogical Discourse, 2017)
The article deals with the process of lecturers’ professional self-improvement. The aim of the article was to review the ways of lectures’ professional self-improvement at higher educational establishments. The author claims that this problem is important, topical and needs contemporary ways of its analyse. Several methods have been used during the article preparation such as: system analysis of documents and scientific researches of the problem investigated, with the help of which the possible aspects of the problem’s examination have been revealed; terminological analysis, which was useful in the process of identification of different approaches to the term «professional self-improvement». In the article the essence of the concept «professional self-improvement» and its basic features have been analysed. Conditions that cause the development of lectures’ professional self-improvement have been distinguished. They are: capability for reflection; self-organization; usage of common forms of activity; involvement in different forms of educational activities; opportunities for comparing and evaluating professionally important qualities and skills; formation of right assessment attitude towards themselves and others.The processes of self-education and self-developement have been considered as the basic components of the self-improvement process. A concept «pedagogical reflection» as the quality feature of lectures’ readiness to the realization of pedagogical activity has been analysed. The main forms of lectures’ professional self-improvement have been considered.It has been concluded that the improvement of the mechanism of lectures’ professional self-improvement assists to develop lectures’ confidence in professional activity, persistence in gaining pedagogical solutions, ability to regulate the emotional state and concentrate upon the realization in profession. The author underlines that lectures’ professional self-improvement is the constant systematic work upon themselves.Key words: professional self-improvement, self-developement, self-education, pedagogical reflection.